2011
DOI: 10.1016/j.joen.2011.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Survey of General Dentists to Identify Characteristics Associated with Increased Referrals to Endodontists

Abstract: There are concrete actions endodontists can take and segments of the GP population that can be targeted to successfully address the issue of increasing referrals, but this is only the first step in addressing the complex relationships involved in referral behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
0
11
1
1
Order By: Relevance
“…This does seem to be a recurring theme in most of the literature to date: although an analysis of dental claims data in Washington State revealed no gender differences in practice patterns [ 21 ], other studies have observed that male dentists are more likely to provide specific procedures. These include studies of Nova Scotia and Virginia GDs in which male dentists were more likely to perform non-surgical periodontal therapy [ 8 , 14 ], endodontic services [ 11 ], and dental extractions [ 12 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This does seem to be a recurring theme in most of the literature to date: although an analysis of dental claims data in Washington State revealed no gender differences in practice patterns [ 21 ], other studies have observed that male dentists are more likely to provide specific procedures. These include studies of Nova Scotia and Virginia GDs in which male dentists were more likely to perform non-surgical periodontal therapy [ 8 , 14 ], endodontic services [ 11 ], and dental extractions [ 12 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Periodontal referrals have been associated with year of dental school graduation [ 13 , 18 ]. Endodontic referrals were less likely among GDs with 6–10 years of experience, compared to those with more than 10 years of experience [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few surveys of general dental practitioners have been conducted to determine the various factors associated with a referral to an endodontist 1,2,3,4,5. One of these surveys demonstrated the various aspects regarding the relationships between general practitioners and endodontists, such as communication, location, patient management, and waiting time, influenced decisions pertaining to endodontic referrals 2.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent past, there have been surveys conducted from the GP's perspective analyzing the referral relationship, which have shown concrete actions endodontists could potentially take to increase their referral base and improve their referral relationship (16,17). However, to the authors' knowledge no study has examined U.S. endodontists' perceptions regarding the referral relationship and endodontic economics.…”
mentioning
confidence: 99%